(3OjhGf GHf GdUHGZs - (3CHhYHO Gddg eMeO Hf CMeO Hf GdUHGZ GdLPGejs
(3ChdgG (B:s
(3Chd bUjOI aj eOM GdfHj Udi Gddg Ydjg hSde(B: (3CPcJ HCMfGA GdVdhY EhGQG hQb JQLY TOhgG CSMGQG s
(3BNQgG (B:s
(3eHJhQ hjfJgj CKfGA ehTMI YfhGfgG (B((3hef JacjQ GdYLjH aj GdSgQ(B) (3aGTJfTbhG fSjeg hYGfbhG CZUGfg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B140 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdedcjI HGdQHGW (B(109) s
Keywords: (3GdCOHs